FRI0528 Canakinumab in Systemic Juvenile Idiopathic Arthritis: Impact on the Rate and Clinical Presentation of Macrophage Activation Syndrome. (10th June 2014) - Grom, A.A.; Brunner, H.I.; Ruperto, N.; Martini, A.; Lovell, D.; Pascual, V.; Lheritier, K.; Abrams, K.; Ilowite, N.
Abstract : Background: Canakinumab is a fully human, selective, anti-IL-1β monoclonal antibody approved for the treatment of patients with systemic juvenile idiopathic arthritis (SJIA). In the phase III trials, macrophage activation syndrome (MAS), a potentially fatal complication of SJIA, was reported as an adverse event (AE) in both canakinumab and placebo group patients. This prompted Novartis to form an independent expert MAS Adjudication Committee (MASAC) to develop methodology to identify and review potential MAS events. Objectives: To assess the impact of canakinumab on incidence of MAS in SJIA patients. Methods: A periodic search of the canakinumab SJIA clinical study databases and the separate serious AE safety database was performed using MASAC-specified screening AE terms (cut-off date 31 May 2012). MASAC-specified laboratory criteria were also used to search clinical study databases. MAS events were then adjudicated blinded to treatment by the MASAC as either probable, possible, or unlikely MAS, or insufficient information loosely based on the diagnostic criteria by Ravelli et al. 2 and personal experience. MAS rates were expressed as numbers of probable or possible MAS events per 100 patient-years (pt-yr). Results: Forty-three potential MAS events were identified for adjudication (12 reported as MAS AEs and 31 by screening database searches). Nine events were adjudicated as probable, 5 as possible and 29 as unlikely MAS. Of the 9 probable MAS events, 7 occurred in the canakinumab and 2 in the placebo group, and all were also reported as a MAS AE by the treating physician. SJIA was well controlled in all 7 canakinumab patients and all developed classic clinical features of MAS. Of the 7 canakinumab patients, 6 reported MAS in the setting of an active infection. The MAS events were not associated with a change in concomitant therapy. The time period between the first injection of canakinumab and the onset of MAS ranged between 13 days to 1.7 years (median, 83 days). The rate for MASAC adjudicated probable MAS was 2.5/100 pt-yr and 7.7/100 pt-yr for the canakinumab and placebo groups, respectively with no statistically significant difference between groups (diff=-5.2, 95% CI, -16.0, 5.7). When events adjudicated as either probable or possible MAS were combined, the rate for the canakinumab group was 4.3/100 pt-yr and 7.7/100 pt-yr for the placebo group with no between-group difference (diff=-3.4, 95% CI, -14.3, 7.6). Five of the 7 patients adjudicated as probable MAS recovered completely and 2 (1 canakinumab and 1 placebo) died from complications of MAS and/or infection. Conclusions: Canakinumab does not appear to have an effect on the incidence of MAS or its clinical presentation. MAS occurred even in those patients in whom underlying SJIA was well controlled with canakinumab treatment. As often seen in MAS, active infection was the most common associated trigger in this group. References: Ruperto N, et al.N Engl J Med 2012;367(25):2396-406. Ravelli A, et al.J Pediatr.2005;146(5):598-604. Disclosure of Interest: A. Grom Consultant for: Novartis, Roche, NovImmune, H. Brunner Consultant for: Novartis, Roche, Janssen, Astrazenca, UCB, Celegene, Pfizer, GSK, Speakers bureau: Novartis, N. Ruperto Grant/research support: To Gaslini hospital from Abbott, Astrazeneca, BMS, Centocor Research and developement, Eli Lilly and company, "ranscesco Angelini", GSK, Italfarmaco, Novartis, Pfizer, Roche, Sanofi Aventis, Schwarz Biosciences GmBH, Xoma, Wyeth, Speakers bureau: Astrazeneca, Bristol Myers and Squibb, Janssen Biologics B.V., Roche, Wyeth, Pfizer, A. Martini Grant/research support: From Bristol Myers and Squibb, Centocor Research & Development, Glaxo Smith & Kline, Novartis, Pfizer Inc, Roche, Sanofi Aventis, Schwarz Biosciences GmbH to Gaslini hospital to support PRINTO research activities, Consultant for: From Bristol Myers and Squibb, Centocor Research & Development, Glaxo Smith and Kline, Novartis, Pfizer Inc, Roche, Sanofi Aventis, Schwarz Biosciences GmbH to Gaslini hospital to support PRINTO research activities, Employee of: Gaslini hospital, Speakers bureau: Abbott, Bristol Myers Squibb, Astellas, Boehringer, Italfarmaco, MedImmune, Novartis, NovoNordisk, Pfizer, Sanofi, Roche, Servier, D. Lovell Grant/research support: National Institutes of Health- NIAMS, Consultant for: Astra-Zeneca, Centocor, Amgen, Bristol Meyers Squibb, Abbott, Pfizer, Regeneron, Roche, Novartis, UCB, Forest Research Institute, Horizon, Johnson & Johnson, Speakers bureau: Novartis, Roche, V. Pascual Consultant for: Served on the MAS adjudication committee for Novartis and is an author on the following patent: # 8221748; Compositions and methods for the treatment of systemic onset juvenile idiopathic arthritis with IL1 antagonists (issued on 7/17/2012), Speakers bureau: Served on the MAS adjudication committee for Novartis and is an author on the following patent: # 8221748; Compositions and methods for the treatment of systemic onset juvenile idiopathic arthritis with IL1 antagonists (issued on 7/17/2012), K. Lheritier Shareholder of: Novartis, Employee of: Novartis Pharma AG, K. Abrams Shareholder of: Novartis, Employee of: Novartis Pharmaceutical Corporation, N. Ilowite Consultant for: Novartis, Janssen DOI: 10.1136/annrheumdis-2014-eular.3070